An Old Dog with New Tricks: Enjoin Wolff–Kishner Reduction for Alcohol Deoxygenation and C–C Bond Formations - Li, Chao-Jun; Huang, Jianlin; Dai, Xi-Jie; Wang, Haining; Chen, Ning; Wei, Wei; Zeng, Huiying; Tang, Jianting; Li, Chenchen; Zhu, Dianhu; Lv, Leiyang (Synlett, 2019)
The Wolff–Kishner reduction, discovered in the early 1910s, is a fundamental and effective tool to convert carbonyls into methylenes via deoxygenation under strongly basic conditions. For over a century, numerous valuable chemical products have been synthesized by this classical method. The reaction proceeds via the reversible formation of hydrazone followed by deprotonation with the strong base to give an N-anionic intermediate, which affords the deoxygenation product upon denitrogenation and protonation. By examining the mechanistic pathway of this century old classical carbonyl deoxygenation, we envisioned and subsequently developed two unprecedented new types of chemical transformations: a) alcohol deoxygenation and b) C–C bond formations with various electrophiles including Grignard-type reaction, conjugate addition, olefination, and diverse cross-coupling reactions.1 Introduction2 Background3 Alcohol Deoxygenation3.1 Ir-Catalyzed Alcohol Deoxygenation3.2 Ru-Catalyzed Alcohol Deoxygenation3.3 Mn-Catalyzed Alcohol Deoxygenation4 Grignard-Type Reactions4.1 Ru-Catalyzed Addition of Hydrazones with Aldehydes and Ketones4.2 Ru-Catalyzed Addition of Hydrazone with Imines4.3 Ru-Catalyzed Addition of Hydrazone with CO24.4 Fe-Catalyzed Addition of Hydrazones5 Conjugate Addition Reactions5.1 Ru-Catalyzed Conjugate Addition Reactions5.2 Fe-Catalyzed Conjugate Addition Reactions6 Cross-Coupling Reactions6.1 Ni-Catalyzed Negishi-type Coupling6.2 Pd-Catalyzed Tsuji–Trost Alkylation Reaction7 Other Reactions7.1 Olefination7.2 Heck-Type Reaction7.3 Ullmann-Type Reaction8 Conclusion and Outlook
Keywords: alkylation; carbanions; catalysis; cross-coupling; deoxygenation; Grignard reaction; hydrazones; nucleophilic addition